Lady Macbeth [videorecording (DVD)] - Pugh, Florence, 1996-; Jarvis, Cosmo; Hilton, Paul, 1970-; Leskov, N. S. (Nikolaĭ Semenovich), 1831-1895 (Lions Gate Entertainment, 2017)
Rural England, 1865. Katherine is stifled by her loveless marriage to a bitter man twice her age, whose family are cold and unforgiving. When she embarks on a passionate affair with a young worker on her husband's estate, a force is unleashed inside her, so powerful that she will stop at nothing to get what she wants.